Green Light! : Men of the 81st Troop Carrier Squadron Tell Their Story - Wolfe, Martin (University of Pennsylvania Press, 2016)
In Green Light! Martin Wolfe gives us the big picture of World War II airborne warfare in Europe through the lens of one unit. Wolfe's firsthand account is an engaging and informative narrative that goes beyond the facts to investigate the feelings of the tightly knit unit.
Keywords: Wolfe, Martin.; United States. -- Army Air Forces. -- Troop Carrier Squadron, 81st -- History.; Wolfe, Martin; United States. -- Army Air Forces. -- Troop Carrier Squadron, 81st; World War, 1939-1945 -- Regimental histories -- United States.; World War, 1939-1945 -- Campaigns -- Western Front.; Guerre mondiale, 1939-1945 -- Histoire des unités -- États-Unis.; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Front occidental.; BIOGRAPHY & AUTOBIOGRAPHY -- Military.; Military campaigns; Regimental histories; United States; Western Front (World War (1939-1945)); 1939-1945; History